Could sound be used as a strategy for reducing symptoms of perceived motion sickness? - Dahlman, J.; Sjörs, A.; Ledin, T.; Falkmer, Torbjorn (2008)
Background. Working while exposed to motions, physically and psychologically affects a person. Traditionally, motion sickness symptom reduction has implied use of medication, which can lead to detrimental effects on performance. Non-pharmaceutical strategies, in turn, often require cognitive and perceptual attention. Hence, for people working in high demand environments where it is impossible to reallocate focus of attention, other strategies are called upon. The aim of the study was to investigate possible impact of a mitigation strategy on perceived motion sickness and psychophysiological responses, based on an artificial sound horizon compared with a non-positioned sound source. Methods. Twenty-three healthy subjects were seated on a motion platform in an artificial sound horizon or in non-positioned sound, in random order with one week interval between the trials. Perceived motion sickness (Mal), maximum duration of exposure (ST), skin conductance, blood volume pulse, temperature, respiration rate, eye movements and heart rate were measured continuously throughout the trials. Results. Mal scores increased over time in both sound conditions, but the artificial sound horizon, applied as a mitigation strategy for perceived motion sickness, showed no significant effect on Mal scores or ST. The number of fixations increased with time in the non-positioned sound condition. Moreover, fixation time was longer in the non-positioned sound condition compared with sound horizon, indicating that the subjects used more time to fixate and, hence, assumingly made fewer saccades. Conclusion. A subliminally presented artificial sound horizon did not significantly affect perceived motion sickness, psychophysiological variables or the time the subjects endured the motion sickness triggering stimuli. The number of fixations and fixation times increased over time in the non-positioned sound condition.